Evaluation of Antioxidant Effect of Spices and Condiment Mix as Nitrite Replacer in Chicken Mince - Goswami, M.; Prabhakaran, P.P.; Tanwar, V.K. (Journal of Meat Science, 2014)
The present study was carried out to compare the antioxidant effect of spices and condiments mix with nitrite added to chicken mince stored at 4±10C. The treatments include control (C), turmeric added @ 1000ppm (T), heated turmeric (1200C for 15 min on hot plate added @1000 ppm (HT), turmeric @1000 ppm added along with 4% gingar and 4% garlic (GGT), meat masala (Agmark “Catch Masala”) added @ 1000 ppm (MM) and sodium nitrite added @ 200 ppm (N).Physico-chemical properties viz. pH, thiobarbituric acid values (TBA) and free fatty acid values (FFA) were evaluated on 0, 3, 6 and 9th day of storage. All the treatments showed better antioxidant effects than control. Among the treatments, the highest value of pH was found in GGT (5.95±0.02) and the lowest was found in T (5.86±0.04). In TBA, the lowest value was found in HT (0.55±0.09) and the highest was observed in T (0.65±0.11) among the treatments. The lowest PV among the treatments was found in HT (1.56±0.17) and the highest value was observed in N (2.03±0.21). The lowest FFA value was observed in HT (1.17±0.19) and T (1.58±0.33) had the highest FFA among the treatments. Heat treated turmeric and ginger garlic turmeric paste had the best antioxidant properties can be used as nitrite replacer for natural anti-oxidants in complex food like chicken mince.
Keywords: Fat oxidation; Garlic; Ginger; Heated turmeric